Description of a new species of Echiodon (Teleostei: Carapidae) from the South Atlantic Ocean - Anderson, M. Eric (Zootaxa, 2005)
A new species of pearlfish, Echiodon atopus, is described from a single adult male, 176 mm TL, collected off Inaccessible Island, Tristan da Cunha Group, South Atlantic Ocean. It is characterized by its high, equal D 30 and A 30 counts (46 rays each), 7 anal rays anterior to the dorsal-fin origin, 38 precaudal vertebrae, 18 pectoral-fin rays and ventral swim bladder tunic ridges. It was caught in a bottom trawl over a deep lava-reef structure, but may be pelagic.